Nutritive solutions for the hydroponic germination of Hordeum vulgare - Ordoñez, Edson (2018)
The objective of the study was to determine the effect of different doses of nutritive solutions A and B in the water of barley hydroponic fodder (Hordeum vulgare) on the nutritional value and germination performance. Six treatments were used: Control - T0: without solution A and B; T1: 1.00 ml A and 0.50 ml B: T2: 0.50 ml A and 0.125 ml B; T3: 0.75 ml A and 0.25 ml B; T4: 1.25 ml A and 0.75 ml B; T5: 1.50 ml A and 1.00 ml B, all with six repetitions per treatment. The results of the proximal chemical analysis and germination yield were subjected to a completely randomized design. The doses of nutritive solutions significantly affected all the evaluated variables, with T3 showing the best values of the evaluated variables except for the ash content, while T0, T4 and T5 showed the lowest values. Therefore, it is concluded that the combination of nutritive solutions in doses of 0.75 ml A and 0.25 ml B is the most appropriate to obtain better results on the performance and nutritional value of barley hydroponic germination.